2021
DOI: 10.1021/acsmaterialslett.1c00474
|View full text |Cite
|
Sign up to set email alerts
|

Defect Behaviors in Perovskite Light-Emitting Diodes

Abstract: Defects play a pivotal role in the physical and chemical properties of semiconductor materials. Regulation of the type, distribution, and quantity of defects within the crystal allows for refinement of material properties, which, in turn, affects the performance of semiconductor devices. Looking back at the development in the realm of perovskite, the research on defect behaviors has always been closely linked to the outstanding improvements in solar cells, light-emitting diodes (LEDs), and other devices. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 254 publications
(653 reference statements)
0
22
0
Order By: Relevance
“…Surface defects may facilitate the anion exchange process. 32,33 With the assistance of the DDAC ligand, Cl exchanges with halogens in the [Pb-Br 6 ] 4− octahedron to form [Pb-(Br/Cl) 6 ] 4− (Fig. 1a).…”
Section: Efficient Exchange In Acpb Qdsmentioning
confidence: 99%
“…Surface defects may facilitate the anion exchange process. 32,33 With the assistance of the DDAC ligand, Cl exchanges with halogens in the [Pb-Br 6 ] 4− octahedron to form [Pb-(Br/Cl) 6 ] 4− (Fig. 1a).…”
Section: Efficient Exchange In Acpb Qdsmentioning
confidence: 99%
“…The electrons and holes injected from the cathode and anode under the electric field are transported through the hole transport layer (HTL) and electron transport layer and then confined in MHP EMLs to form excitons before light emission. Moreover, device characteristics, such as current efficiency, external quantum efficiency (EQE), and brightness, are highly dependent on the radiative recombination rate originating from the quality of the MHP thin films because the MHPs have defects, such as halide vacancies and grain boundaries, which act as charge trapping sites during device operation [40,41]. Kumawat et al reported the first blue PeLED using Br-Cl mixed-halide perovskite as emitting layers (EMLs) [37].…”
Section: Mixed-halide Perovskites 21 Electronic Structuresmentioning
confidence: 99%
“…[2,8,9] In addition, MHPs significantly decrease both the economic and energetic costs of film manufacturing owing to their cost-effectiveness and low-temperature solution processability. [10] The first room-temperature PeLEDs were reported in 2014 with low external quantum efficiencies (EQEs) of 0.76% due to the relatively poor morphology of the film and the large number of traps assisted by radiation-free composite. [11] With the rapid development of morphology control, composition engineering, and device engineering, tremendous improvements have been witnessed in the EQE of primary-color PeLEDs.…”
Section: Introductionmentioning
confidence: 99%